Цивилизационные перспективы мирового развития - Стадник, Д. В. (ХНУРЕ, 2021)
The article examines the problems of the civilizational dimension of the development of the modern world in the context of globalization challenges. It is shown that in all generally accepted interpretations, civilization is opposed to chaos, disorder, internal discord and a decline in morals. One of the conditions for the self-preservation and development of civilization is considered a negative attitude towards all kinds of schisms and strife. Any of the civilizational theories proceeds from the fact that the historical process is a movement from the lowest to the highest, to a more perfect existence of a person, culture, society, which provide interaction in a limited range of areas and more rigid alliances that imply interaction of a mandatory nature
Keywords: философия; перспективы мирового развития